The Freeze–Thaw Process and Long Intervals after Fortification Denature Human Milk Fat Globules - Takahashi, Kenichiro; Mizuno, Katsumi; Itabashi, Kazuo (American Journal of Perinatology, 2012)
Although mother’s milk is the optimal nutrition for preterm infants, the amount of protein, calcium, and phosphorus become inadequate for the growth of preterm infants, such that fortification is recommended when enteral feeding is established. Recently, intestinal obstruction due to calcium soap formation has been reported. All the reported cases were fed fortified thawed human milk. It has not been elucidated how human milk fortifier reacts with milk fat globules (MFGs) in thawed human milk. Therefore, we investigated whether freezing durations and time between fortification and enteral feeding denatured MFGs. Six samples of preterm mothers’ milk of each type (fresh unfrozen, 1-month frozen, and 12-month frozen) were analyzed. Fortifier was not added to the control. The samples were measured at 1, 12, and 24 hours after fortification. The MFG size distribution of each milk sample was measured. The freezing process enlarged the mode diameter (4.0 ± 0.4, 4.3 ± 0.7, and 4.5 ± 0.9 in fresh unfrozen milk, 1-month frozen, and 12-month frozen milk, respectively, p < 0.001). Fortification itself did not significantly alter the MFG size in thawed mother’s milk. However, a time lag of 12 hours after fortification enlarged the MFG size and resulted in smaller surface area per unit (3.6 ± 0.2, 3.3 ± 0.1, and 3.3 ± 0.1 m2/g, fresh unfrozen, 1-month frozen, and 12-month frozen, respectively) compared with 0 hours of time lag (3.8 ± 0.2, 3.5 ± 0.1, and 3.4 ± 0.2 m2/g, fresh unfrozen, 1-month frozen, and 12-month frozen, respectively). Not only the freeze–thaw procedure but also time lag after fortification affected MFG size. We recommend using fortified thawed human milk within 12 hours.
Keywords: human milk fortifier; human milk storage; calcium soap